Tick-Borne Encephalitis in Vaccinated Patients: A Retrospective Case-Control Study and Analysis of Vaccination Field Effectiveness in Austria From 2000 to 2018. (2nd March 2022) - Santonja, Isabel; Stiasny, Karin; Essl, Astrid; Heinz, Franz X; Kundi, Michael; Holzmann, Heidemarie
Abstract: Background: There are discrepant observations on the severity of tick-borne encephalitis (TBE) in vaccinated persons. We, therefore, analyzed the occurrence of severe and mild disease in hospitalized vaccinated and nonvaccinated patients with TBE and determined the field effectiveness (FE) of vaccination against these forms of disease. Methods: The study covered all patients hospitalized with TBE in Austria from 2000 to 2018. Clinical diagnoses in vaccinated and age- and sex-matched nonvaccinated patients were compared in a nested case-control study. FE was calculated based on vaccination coverage and incidences in the nonvaccinated and vaccinated population. Results: Of 1545 patients hospitalized with TBE, 206 were vaccinated. In those, a higher proportion of severe TBE was observed, especially in children. FE was high in all age groups and against all forms of disease. The higher proportion of severe TBE can be explained by a lower FE against severe than against mild disease, a difference especially pronounced in children (FE, 82.7% for severe vs 94.7% for mild disease). Conclusions: The FE of TBE vaccination is excellent. The observed higher proportion of severe disease in vaccinated persons with TBE does not reflect a higher risk associated with vaccination but is rather due to a somewhat lower FE against severe TBE. Because this effect was more pronounced in children, we recommend adapting the immunization schedule. Abstract : The higher proportion of severe forms of tick-borne encephalitis (TBE) among vaccinated patients is due to a still-excellent but slightly lower effectiveness of vaccination against severe compared with mild TBE, and not to higher risk associated with TBE vaccination.